E-wallet Adoption in The Covid-19 Period: The Roles Of Perceived Benefits As Mediating Variabel - Nur Asida, Abi Yusuf; Kuswati, Rini (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2023)
This study aims to analyze the effect of ease and convenience of use on e-wallet adoption in the millennial generation in Indonesia and the role of perceived benefits as a mediator. The spread of the Covid-19 virus has an impact on changes in the payment system due to the physical distancing policy. The payment system, which was initially in cash, has become server-based which can be accessed via a website or application (e-wallet). This research method is quantitative. The sampling technique used purposive sampling method. The number of samples in this study were 215 students. The data analysis technique in this study used Partial Least Square (PLS) with the help of SMARTPLS Software. The results of data analysis show that this research instrument has good validity and reliability. The ease and convenience of use has a direct effect on the e-wallet adoption behavior of Indonesia's millennial generation. Perceived benefits have been shown to be a partial mediator in the behavioral model of e-wallet adoption in Indonesia's millennial generation. This novel study shows that the adoption behavior of Indonesia's millennial young generation in adopting e-wallets does not only pay attention to the benefits of e-wallet services, but also as a necessity in this digital technology era. The implications of this research are to provide benefits for knowledge bearers in the field of marketing as a reference for scientific studies on how convenience and convenience influence e-wallet adoption and its relation to perceived benefits, as well as providing information, insights, and references that can add to readers' knowledge.